Graphene in 2D/3D Heterostructure Diodes for High Performance Electronics and Optoelectronics. (27th March 2021) - Wang, Zhenxing; Hemmetter, Andreas; Uzlu, Burkay; Saeed, Mohamed; Hamed, Ahmed; Kataria, Satender; Negra, Renato; Neumaier, Daniel; Lemme, Max C.
Abstract: Diodes made of heterostructures of the 2D material graphene and conventional 3D materials are reviewed in this manuscript. Several applications in high frequency electronics and optoelectronics are highlighted. In particular, advantages of metal–insulator–graphene (MIG) diodes over conventional metal–insulator–metal diodes are discussed with respect to relevant figures‐of‐merit. The MIG concept is extended to 1D diodes. Several experimentally implemented radio frequency circuit applications with MIG diodes as active elements are presented. Furthermore, graphene‐silicon Schottky diodes as well as MIG diodes are reviewed in terms of their potential for photodetection. Here, graphene‐based diodes have the potential to outperform conventional photodetectors in several key figures‐of‐merit, such as overall responsivity or dark current levels. Obviously, advantages in some areas may come at the cost of disadvantages in others, so that 2D/3D diodes need to be tailored in application‐specific ways. Abstract : Diodes made of heterostructures of the 2D material graphene and conventional 3D materials are reviewed in this article. In particular, metal–insulator–graphene diodes and graphene‐silicon Schottky diodes are discussed with relevant figures‐of‐merit. Several applications in high frequency electronics and optoelectronics are highlighted, such as power detectors, mixers, frequency doublers, receivers, and photodetectors.